Cloud Based Smart Agricultural Monitoring System using Internet of Things - Subhra Debdas, Priyasmita Kundu, Sayantan Kundu, Aniket Saha (International Journal of Advanced Science and Technology, 2020)
The Internet of Things (IOT) has brought about a revolution in many of the spheres of our present lives, like automobile, health-care facilities, home automation and many more. The Agriculture and Farming industries have also received a major impact on the introduction of the IOT to the world. Now, the IOT makes real - time collection of data, involving soil moisture content and the status of crops, more convenient through the available IOT sensors. The collected massive data, after being stored, can be analyzed and applied to allow the farmers to solve the problems which come across at the field and thus ensure, a productive cultivation. The IOT also finds use in setting up drones to aid with jobs like pesticide spray and also to regulate the precise working hours of irrigation tanks and motors in compliance with the need of the crops. However, the storage of such a huge amount of data acts as a barrier due to data loss and the complexity involved in offline data storage maintenance. Therefore, to avoid this barrier, we implement cloud computing, which acts as a virtual storage system. In this paper, we study a smart agricultural data monitoring system which collects the required data from the IOT sensors placed in the field, processes it and pushes it into the PUBSUB, from where it flows to store in the Google Cloud Console. The data is then sent to the prediction module where the required analyzation is done and then sent to the user interface for its corresponding application.